Alpha-Gal Syndrome in Children: Peculiarities of a “Tick-Borne” Allergic Disease - Saretta, Francesca; Giovannini, Mattia; Mori, Francesca; Arasi, Stefania; Liotti, Lucia; Pecoraro, Luca; Barni, Simona; Castagnoli, Riccardo; Mastrorilli, Carla; Caminiti, Lucia; Marseglia, Gian Luigi; Novembre, Elio (Frontiers in Pediatrics, 2021)
The alpha-gal syndrome is an allergic syndrome that comprises two clinical pictures: an immediate hypersensitivity to drugs containing alpha-gal and a delayed hypersensitivity to the ingestion of red mammalian meat. This allergic syndrome is often under-recognized, and patients are mislabeled with diagnosis as spontaneous urticaria or idiopathic anaphylaxis. Even though less frequently, children could also be of interest, especially in tick-endemic areas. In most cases, a positive anamnesis for tick bites months before the onset of symptoms is recorded. The clinical manifestations could range from asymptomatic cases to severe anaphylaxis. The most frequently used diagnostic test is the determination of specific IgE for alpha-gal. Oral provocation test is usually reserved to unclear cases or to verify tolerance after diet. No long-term follow-up studies have been published, although an elimination diet could lead to a decrease of specific IgE for alpha-gal and a possible reintroduction of some avoided foods. This paper provides a literature review, focused on pediatric age, and an evaluation of available diagnostic tests. We analyze the correlation between tick bites and symptom onset and unfold the different clinical pictures to help clinicians to promptly recognized this syndrome. Lastly, we address unmet needs in this specific allergy.